地域包括ケア病棟看護師における高齢者の生活を支える看護実践自己評価尺度の開発 - 荒井 葉子; 實金 栄; 名越 恵美 (日本看護科学会誌, 2023)
要旨　目的：地域包括ケア病棟看護師における高齢者の生活を支える看護実践自己評価尺度を開発し，妥当性・信頼性を検証する．　方法：概念分析による高齢者の生活を支える看護の属性と先行研究および質的研究を参考に抽出した7つの看護の特徴から尺度原案を作成した．内容的・表面的妥当性を検討後，全国の地域包括ケア病棟看護師を対象に質問紙調査を実施，尺度の信頼性・妥当性を検証した．　結果：分析対象は457名（有効回答率97.6％），探索的因子分析により6因子23項目からなる尺度を作成した．モデルの適合度はRMSEA＝.053，CFI＝.98であった．併存的妥当性，収束的妥当性と弁別的妥当性も十分な値を示した．Cronbach's α係数は，下位因子で.73〜.89，尺度全体では.93であった．　結論：地域包括ケア病棟看護師における高齢者の生活を支える看護実践自己評価尺度を開発し，妥当性・信頼性が確認された． 　Objective: To develop a self-evaluation scale for nursing practice to support the lives of elderly people and evaluate its validity and reliability.　Methods: We developed a draft of a scale based on the attributes of nursing practice to support the lives of elderly people extracted from conceptual analysis, and seven nursing characteristics that were designed by referring to previous studies and qualitative research. After assessing validity in terms of content and superficially, we conducted a questionnaire survey with ward nurses engaged in hospitals for community-based care and evaluated the credibility and validity of this scale.　Results: The analysis involved 457 subjects (valid response rate: 97.6％). Based on an explorative factor analysis, a scale consisting of 6 factors and 23 items was designed. The adaptability of the model was RMSEA＝.053 and CRI＝.98. The concurrent validity, convergent validity, and distinctive validity were all satisfactory. Regarding Cronbach's α coefficient, the hypostatic factor ranged from 0.73-0.89, and the overall scale was .93.　Conclusion: We developed a self-evaluation scale for nursing practice to support the lives of elderly people in hospitals for community-based care for ward nurses and confirmed its validity and reliability.